New cutting edge: Intermediate. teacher's resource book - Barker, Helen; Moor, Peter, 1957-; Cunningham, Sarah, 1960-. (Harlow : Pearson Education, 2008)
The New Cutting Edge Student Books combine the comprehensive syllabus and reliable teaching resources that have made the course so popular, with brand-new features, making it even fresher and easier to use.
first published 2005.
Keywords: English language -- Textbooks for foreign speakers; English language -- Problems, exercises, etc; English language| -- Spoken English